Breed Effect and Genetic Characterization of the THRSP Gene in Local and Shami Goats - Huda Rahman Fager; Abdullah Hameed Salim (University of Thi-Qar Journal of agricultural research, 2025)
This study was conducted at the Ruminant Research Station affiliated with the Agricultural Research Directorate. The study aimed to investigate the effect of goat breed on body dimension traits (chest circumference, body length, height at the withers, and height at the rump), growth traits (birth weight, weaning weight, average daily gain from birth to weaning, and current weight), and the genetic variation among the studied traits as well as the genetic characterization of the local and Shami goat breeds.The results showed that the studied growth traits were not significantly affected by breed, with no notable differences among the three genotypes (CC, GC, GG) of the targeted gene segment THRSP in the local goats. Similarly, in the Shami goats, no significant differences were observed among the three genotypes for any of the growth traits.Furthermore, the results indicated that there were no significant effects of the three genotypes (CC, GC, GG) resulting from the 322.G>C mutation on body dimension traits in either of the two breeds (local and Shami). It was also observed that the genotype GG had a higher frequency than the other two genotypes (CC and GC) in both local and Shami goats.Regarding the biodiversity indicators for the studied gene THRSP, both local and Shami breeds showed a lower effective allele number compared to the actual allele number. The Shannon-Weiner index showed weak or low values in both breeds. The homogeneity index (E) in both breeds indicated a near-complete homogeneity among genotypes, approaching a value of 1. However, the genetic differentiation index reflected a degree of genetic variation between the two breeds (local and Shami), while the gene flow rate was high, indicating strong gene exchange between the two breeds.